Suplemento : cuadernos de literatura y arte : 1, 15 de enero de 1969 - Flores, Ernesto (edición) (1969)
Contiene obra de: Guillermo García Oropeza, Ricardo Yáñez, Luis Sandoval Godoy, Jaime E. Cuevas y Artemio González García.